Diet Containing Soy Protein Concentrate With Low and High Isoflavones for 9 Weeks Protects Against Non-alcoholic Fatty Liver Steatosis Using Obese Zucker Rats - Hakkak, Reza; Spray, Beverly; Børsheim, Elisabet; Korourian, Soheila (Frontiers in Nutrition, 2022)
Non-alcoholic fatty liver disease (NAFLD), the major cause of abnormal liver function in the US and the world, is often associated with obesity. Previously, we reported short- and long-term consumption of soy protein isolate diet with high isoflavones can reduce liver steatosis in the male and female obese Zucker rat model. However the effects of high vs low soy isoflavones on NAFLD is less known. The objectives of the present study were to examine the role of isoflavones levels in soy protein concentrate diets on protection against NAFLD in an obese rat model. Forty-two 6-week old lean (L, n=21) and obese (O, n=21) Zucker rats were randomly assigned to 1 of 3 dietary groups: casein diet (C=control), soy protein concentrate with low isoflavones (LIF), or soy protein concentrate with high isoflavones (HIF) for 9 weeks. Rats were weighed twice weekly. After 9 weeks, rats were sacrificed and samples of livers were taken for histopathological analysis. Serums were collected to measure ALT and AST levels. Results indicate that obese rats gained significantly more weight than lean rats for all three diet groups P < .001). No significant difference in body weight between LC, LLIF and LHIF was noted. However, the OLIF and OHIF rats gained significantly more weight than OC rats (P < .001). Liver steatosis scores were significantly greater in obese rats compared to lean rats (P < .001). The OLIF and OHIF-fed rats had significantly lower steatosis scores than OC rats (P = .013 and P < .001, respectively). The serum ALT levels were significantly greater in OC, OLIF and OHIF compared to LC, LLIF and LHIF, respectively (P < .001, P < .001, and P = .011). AST serum levels were greater in OC and OLIF compared to LC and LLIF, respectively (P=.001 and P = .022). In summary, we found that soy protein concentrate with isoflavones protects against liver steatosis and the protection is greater with a higher concentration of isoflavones.